Understanding the International Criminal Law of Tomorrow. When Serious and Widespread Corruption that Violates Human Rights Should Be Seen as Crimes Against Humanity at the International Level - Roksandić, Sunčana (The ICC at 25: Lessons Learnt, 2025)
It is recognised that challenges for international criminal law ‘go far beyond armed conflict’. The international community provided the legal answer by creating a crime that protects against serious, widespread and long-term violations of human rights committed by a variety of actions and attacks and that threaten the human dignity of individuals and humanity as a whole – crimes against humanity. Acts considered crimes against humanity are capable of long-term and widespread human rights infringement, thereby endangering the peace, security and well-being of the world. The category of crimes against humanity empowers the international community with a tool to respond to the gravest violations of human rights.However, of particular global concern, according to the author, should be that serious economic crimes (systematic and large-scale corruption) and deprivation of essential medicine and health care, as well as environmental crimes are not yet seen as crimes against humanity although elements of Article 7(1) (k) of the International Criminal Court’s Statute offer the possibility of such an interpretation. Many claim that economic and social rights have often been neglected in terms of the protection offered by international criminal law.In this article, the author builds upon her previous research and texts which are used throughout this contribution, and provides, primarily for the scientific and expert community of Central European countries, her main arguments already published in extenso. The author is of the opinion that construction of crimes against humanity in today’s realities should be discussed more (with pro and contra arguments) in Central Europe. The conference The ICC at 25: Lessons Learnt, Might Have Been Learnt and Unlearnt provided a platform for the exchange of ideas among scholars and experts in Central Europe. The author was invited to present her research to this conference, thereby opening up the topic for the discussion in the region.This contribution provides key legal arguments in a concise manner for the international criminalisation of serious and widespread crimes involving corruption as crimes against humanity.Keywords: Economic crimes, serious and widespread corruption, UNCAC, International Criminal Court (ICC), crimes against humanity